노인 환자에서 Vancomycin 사용과 관련한 신독성의 위험인자 연구 - 김하늬; 김해숙; 이양현; 이경주; 신승우; 박선철; 이유정 (한국임상약학회지, 2017)
Objective: Infection is very common in the elderly, so there is a high prevalence of antibiotics use among this population. Especially, due to the emergence of resistant bacteria, the use of vancomycin is growing. The purpose of this study was to evaluate risk factors associated with vancomycin-induced nephrotoxicity in elderly patients. Methods: The subjects of this study were patients over 18 years old who received intravenous vancomycin in a general hospital located in Gangneung-si, Korea between August 1, 2013 and July 31, 2015. Data collection regarding vancomycin use and baseline characteristics was conducted using computerized hospital database. Logistic regression analysis was used to identify risk factors associated with vancomycin-induced nephrotoxicity. Results: A total of 290 patients were finally included, and 191(66%) out of these patients were age 65 or older. The incidence of vancomycin-induced nephrotoxicity was 11.0%, 12.6%, and 7.0% in the all adult patients, the elderly patients, and the non-elderly patients, respectively. There were significant differences in comorbidities between patients with nephrotoxicity and patients without nephrotoxicity in the all adult patients, and there were significant differences in vancomycin duration, comorbidities, and number of nephrotoxic agents between patients with nephrotoxicity and patients without nephrotoxicity in the elderly patients. However, according to the logistic regression analysis, there was no significant risk factor that increases the incidence of vancomycin-induced nephrotoxicity in all three age groups. Conclusion: There were no differences in risk factors that increase the incidence of vancomycin-induced nephrotoxicity between all adult patients, elderly patients, and non-elderly patients. Further studies with larger sample sizes to identify risk factors associated with vancomycin-induced nephrotoxicity in the elderly to improve the outcome of pharmacotherapy are required.